Induction motors with copper rotor: a new opportunity for increasing motor efficiency - Percy R. Viego Felipe; Vladimir Sousa Santos; Julio R. Gómez Sarduy; José P. Monteagudo Yanes; Enrique Ciro Quispe (International Journal of Electrical and Computer Engineering (IJECE), 2023)
The copper rotor induction motor (CURIM) was recently introduced because it has lower rotor fusion losses than the aluminum rotor (ALRIM). Furthermore, with CURIM, it is easier to reach IE4 and IE5 efficiency levels. The CURIM is advantageous for compact motors, escalators, and electric vehicle applications. However, CURIMs present slip, power factor, temperature increase, and torque decrease problems that must be analyzed. This study compared the economic feasibility of using CURIM with ALRIM by applying discount techniques. A case study was carried out in a sugar company with a cyclical operation, where 5.5 kW motors will be installed in the intermediate conductors of the mill's feeders. The facility works three shifts between 3 and 6 months. The cost increase (DCI) of CURIM over ALRIM was between 1.1 and 1.5 times. With 3,600 h/year and 4,000 h/year of operation, the DCI greater than 10%, it was found that the payback is more than four years, and the net present value (NPV) grows linearly.